TLC Screening and Evaluation of Antioxidant, Antibacterial Activity of Onopordon Macrocephalum by Bioautography Method: TLC Screening and Bioautography of Onopordon macrocephalum - Samah Sharif; Adawia Kitaz; Rawaa Al-Kayali (Iranian Journal of Pharmaceutical Sciences, 2016)
Onopordon known as scotch thistle is a medicinal plant of the Asteraceae family that is widely distributed in Europe and Asia, also it has many valuable medicinal properties as hypotensive and antitumor. Thin layer chromatography (TLC) is wildly used in natural product extract analysis as a finger print which can be used for identification and quality control of medicinal preparations. Performing Thin-layer chromatography TLC tests on the plant shows the presence of flavonoids, coumarins, and bitter principles. Planar chromatographic analysis hyphenated with the biological detection method is known as bioautography which is an effective and inexpensive technique for the phytochemical analysis of plant extracts. Thin-layer chromatography-direct bioautography links separation on the adsorbent layer with biological tests performed directly on it in order to identify antimicrobial and antioxidant activities. Bioautography revealed that Staphylococcus aureus was inhibited by most of the flavonoids separated on the TLC plates. Similarly, growth of the Bacillus cereus was also inhibited by one flavonoid band on TLC. Antioxidant bioautography shows the strong antioxidant activity of one flavonoid band, whereas no activity detected of bitter principles. Bioautography showed that the antimicrobial and antioxidant activity was probably due to flavonoids.